De mooiste kastelen van België - De Visscher, Albert (Brussel : Reader's Digest, 1984)
Aigremont - Aldenbiezen - Annevoie - Antoing - Arenberg - Attre - Beauvoorde - Beerlegem - Beerse - Beloeil - Berzee - Boethe - Bois-de-Lessines - Bonlez - Bossenstein - Bouillon - Chantraine - Chimay - enz.
Keywords: Castles -- Belgium